Telegram Development in Dokeos-Based E-Learning As a Learning Media to Improve Students' Motivation in Learning Physics - Winarto, Anton; Hardyanto, Wahyu; Sugianto, Sugianto (Universitas Negeri Semarang, 2019)
Telegram Development in Dokeos-Based E-Learning as a Learning Media to Increase Students' Learning Motivation in Physics Subjects. The purpose of this study are to: (1) Determine the development of telegram in Dokeos-based e-learning as a learning media to increase students' motivation in physics subjects. (2) Analyse the effect of Telegram development learning media on dokeos-based e-learning to students' motivation. (3) Know the practicality of telegram learning media on dokeos-based e-learning according to the students. (4) Know the practicality of telegram learning media on dokeos-based e-learning according to the teacher. The type of this research is Research and Development (R&D). The results showed that: (1) Telegram learning media on dokeos-based e-learning were developed through seven stages, namely: needs and literature analysis, product design, product development, small-scale trials, product revisions, large-scale trials, and the final product. The learning media developed at the